“I act, and I know that I am the one who acts”: What is Agency? How is it manifested? - Grigoryan, Ani (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article is devoted to the analysis of the neuroscientific and psychological main approaches to the study of agency. Definitions of different authors are presented. An attempt has been made to outline the main peculiarities of the manifestation of agency that can serve as a basis for empirical study.